The application of short-term efficiency analysis in diagnosing occupational voice disorders - Ewa Niebudek-Bogusz; Marcin Just; Michał Tyc; Justyna Wiktorowicz; Joanna Morawska; Mariola Śliwińska-Kowalska (Nofer Institute of Occupational Medicine, 2015)
Background: An objective determination of the range of vocal efficiency is rather difficult. The aim of the study was to assess the possibility of application of short-term acoustic efficiency analysis in diagnosing occupational voice disorders. Material and Methods: The study covered 98 people (87 women and 11 men) diagnosed with occupational dysphonia through videostroboscopic examination. The control group comprised 100 people (81 women and 19 men) with normal voices. The short-term acoustic analysis was carried out by means of DiagnoScope software, including classical parameters (Jitter group, Shimmer group and the assessment of noise degree NHR), as well as new short-term efficiency parameters determined in a short time period during sustained phonation of the vowel "a." The results were then compared. Results: The values of all the examined classical parameters were considerably higher in the study group of pathological voices than in the control group of normal voices (p = 0.00). The aerodynamic parameter, maximum phonation time, was significantly shorter by over 0.5 s in the study group than in the control group. The majority of the acoustic efficiency parameters were also considerably worse in the study group of subjects with occupational dysphonia than in the control group (p = 0.00). Moreover, the correlation between the efficiency parameters and most of the classical acoustic parameters in the study group implies that for the voices with occupational pathology the decreased efficiency of the vocal apparatus is reflected in the acoustic voice structure. Conclusions: Efficiency parameters determined during short-term acoustic analysis can be an objective indicator of the decreased phonatory function of the larynx, useful in diagnosing occupational vocal pathology. Med Pr 2015;66(2):225-234